Development of severe intrapulmonary shunting in a patient with carcinoid heart disease after closure of a persistent foramen ovale: a case report. Issue 12 (4th December 2021) - Schüttler, Dominik; Mourouzis, Konstantinos; Auernhammer, Christoph J; Rizas, Konstantinos D
Abstract: Background: Neuroendocrine tumours (NETs) can affect the cardiopulmonary system causing carcinoid heart disease (CHD) and valve destruction. Persistent foramen ovale (PFO) occlusion is indicated in patients with CHD and shunt-related left heart valve involvement. Case summary: We report the case of a 54-year-old female patient with metastatic NET originating from the small bowel. The patient was on medication with octreotide and telotristat. One year after diagnosis, cardiac involvement of carcinoid developed with regurgitation of right-sided and, due to PFO, left-sided heart valves. Closure of PFO was performed (Occlutech 16/18 mm). One year later, she presented with recurrent severe dyspnoea. The PFO occluder was in situ without residual shunt. Valvular heart disease, including left-sided disease, and metastatic spread of NET were stable. Blood gas analysis revealed arterial hypoxaemia (pO2 = 44 mmHg/5.87 kPa), which was related to extensive intrapulmonary shunting (31% shunt fraction) confirmed using contrast-enhanced echocardiography. The patient was prescribed long-term oxygen supplementation as symptomatic therapy and anti-tumoural therapy was intensified with selective internal radiotherapy (SIRT) of the liver metastases to improve biochemical control of the carcinoid syndrome. At a follow-up visit 4 months after SIRT, the patient-reported stable dyspnoea; however, magnetic resonance imaging revealed progression of osseous metastases. Discussion: An echocardiographic assessment of the presence of a PFO is recommended in patients with NET as PFO closure minimizes the risk of left-sided carcinoid valve disease. Deterioration of symptomatic status in metastasized NET might also be due to a hepatopulmonary-like physiology with intrapulmonary shunting and arterial desaturation thought to be caused by vasoactive substances secreted by the tumour. This is a rare case describing the development of this syndrome after PFO closure.